Regulation of Epigenetic Modifiers, Including KDM6B, by Interferon-γ and Interleukin-4 in Human Macrophages - Yıldırım-Buharalıoğlu, Gökçe; Bond, Mark; Sala-Newby, Graciela B.; Hindmarch, Charles C. T.; Newby, Andrew C. (Frontiers in Immunology, 2017)
Background. Interferon-γ (IFN-γ) or interleukin-4 (IL-4) drive widely different transcriptional programmes in macrophages. However, how IFN-γ and IL-4 alter expression of histone modifying enzymes involved in epigenetic regulation and how this affects the resulting phenotypic polarization is incompletely understood. Methods and Results. We investigated steady state messenger RNA levels of 84 histone modifying enzymes and related regulators in colony stimulating factor-1 differentiated primary human macrophages using quantitative polymerase chain reaction. IFN-γ or IL-4 treatment for 6 to 48 hours changed 11 mRNAs significantly. IFN-γ increased CIITA, KDM6B and NCOA1 and IL-4 also increased KDM6B by 6 hours. However, either cytokine decreased AURKB, ESCO2, SETD6, SUV39H1 and WHSC1, whereas IFN-γ alone decreased KAT2A, PRMT7 and SMYD3 mRNAs only after 18 hours, which coincided with decreased cell proliferation. Rendering macrophages quiescent by growth factor starvation or adenovirus-mediated over-expression of p27kip1 inhibited expression of AURKB, ESCO2, SUV39H1 and WHSC1 and mRNA levels were restored by overexpressing the S-phase transcription factor E2F1, implying their expression, at least partly, depended on proliferation. However, CIITA, KDM6B, NCOA1, KAT2A, PRMT7, SETD6 and SMYD3 were regulated independently of effects on proliferation. Silencing KDM6B, the only transcriptional activator upregulated by both IFN-γ and IL-4, pharmacologically or with short hairpin RNA, blunted a subset of responses to each cytokine. Conclusions. These findings demonstrate that IFN-γ or IL-4 can regulate the expression of histone acetyl transferases and histone methyl transferases independently of effects on proliferation and that up-regulation of the histone demethylase, KDM6B, assists phenotypic polarization by both cytokines.